Hypothetical Scenarios on the Development Model of the Circular Economy in Touristic Destinations - Jeŕom̂e Kuf̈fer; Vincent Grez̀es; Sandra Grez̀es-Bur̈cher (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
The tourism industry is facing many challenges, including reducing the ecological impact of its activities. To adapt to it, some tourism destination stakeholders have undertaken actions that increase the resilience of the local tourism ecosystem by reducing resource consumption while satisfying the demand expressed by their customers to consume more sustainable tourism offers. This paper presents a study on the implementation of circular economy principles in tourism, focusing on two destinations in Valais, Switzerland: Crans-Montana and Pfyn-Finges. By examining sustainable practices and fostering collaboration between tourism and other industries, the research identifies best practices and hypothetical scenarios to enhance regional sustainability and resilience. The findings suggest that systemic approaches, emphasizing resource efficiency and closed-loop production, can significantly benefit tourism ecosystems, promoting economic diversification, environmental sustainability, and cultural preservation. The study contributes to the ongoing discourse on integrating Circular Economy principles into tourism, offering insights and recommendations for policymakers and industry stakeholders to foster more sustainable and resilient tourism models. A benchmark of the best practices of Circular Economy at the international level allows us to highlight the main material flows exchanged between the tourism value chain and its related industries, providing a promising outlook for the future of the tourism industry.
Keywords: Q01; L83; Z32; 330; circular economy; tourism; ecosystem; resilience; inintersectoral collaboration; systemic design